Persepsi Nilai Pelanggan dan Kepuasan di Klinik Swasta "X" di Surabaya - Mohammad Rahman Hakim (Universitas Airlangga, 2017)
The increasing number of health service industry caused an increase of health service demand. Keeping service quality is a main key to give good service to patient. One of service quality measurement methods is through patient satisfaction measurement. To service quality which given by health service facility this research aim to identify patient satisfaction toward service quality in Clinic "X" in Surabaya. The research has been implemented with cross sectional design using quantitative approach. The research use questionnaire which given to 89 patients. On patient service quality satisfaction, patient satisfaction toward interaction, service environment and outcome quality is in stratified category. Total satisfaction in stratified category too. Perceived customer value is in good category. Satisfaction on aspect interaction quality and outcome quality is significantly related to perceived customer value. Total satisfaction is significantly related too with perceived customer value.   Keywords: customer value, quality, satisfaction, service